Hemispheric asymmetry in recent stratospheric age of air changes - K. Dubé; S. Tegtmeier; F. Ploeger; K. A. Walker (Atmospheric Chemistry and Physics)
Many stratospheric trace gases, including O3, HCl, and NOy, have had opposing trends in the Southern Hemisphere (SH) compared to the Northern Hemisphere (NH) during the last 2 decades. Some of this difference is due to hemispherically asymmetric changes in the rate of transport by the Brewer–Dobson circulation (BDC), and some is due to ozone depletion and recovery. The mean age of air (AoA) is a common proxy for the transport rate by the BDC in models; however it cannot be directly measured. We use observations from the Atmospheric Chemistry Experiment Fourier transform spectrometer (ACE-FTS) along with results from the Chemical Lagrangian Model of the Stratosphere (CLaMS) to derive AoA anomalies and AoA trends. The AoA is derived using observations of N2O, CH4, and CFC-12, all long-lived trace gases with tropospheric sources. We also consider CLaMS simulations driven with four different reanalyses (ERA5, ERA-Interim, JRA-55, MERRA-2). We find that, irrespective of which trace gas or reanalysis is used, air in the NH aged by up to 0.3 years per decade relative to the SH over 2004–2017. The maximum hemispheric difference in aging occurs in the middle stratosphere, near 30 hPa (∼ 24 km). We also show that the aging rate in the NH becomes smaller when the analysis is extended to 2021. The observed aging in the NH middle stratosphere contradicts model predictions of a decrease in stratospheric AoA in response to rising atmospheric greenhouse gas levels. However, the smaller aging rate during 2004–2021 compared to 2004–2017 provides some evidence that the NH aging is impacted by decadal variability and the limited length of the observation period.